Students’ Errors in Exponential and Logarithmic Functions: An Error Analysis Using AVAEM Categories - Ramadhanti, Febi Tasya (Absis: Mathematics Education Journal, 2025)
This study aims to analyze students' errors in exponential and logarithmic functions using the AVAEM error category framework: ARITH, VAR, AE, EQS, and MATH. A qualitative method with a case study approach was employed. Thirty-four tenth-grade students from a high school in Samarinda City were involved as research subjects. Data were collected through written tests and interviews with representatives from each error category. The identified AVAEM errors included: 1) ARITH—errors in understanding the rules of operations and properties of exponents and logarithms; 2) VAR—errors in understanding the meaning and role of variables; 3) AE—errors in seeing the structure of algebraic expressions; 4) EQS—misinterpreting the “=” sign as procedural instead of equality; and 5) MATH—errors in vertical and horizontal mathematization. These errors largely stem from difficulties in applying exponent and logarithm properties, memorizing formulas without conceptual understanding, and correctly modeling equations. Consequently, this study offers a valuable starting point for investigating students' learning obstacles, providing a basis for creating a didactical design to help teachers guide students in overcoming them.